[Cost-effectiveness analysis of ocriplasmin in the treatment of vitreomacular traction in Italy] - D'Angiolella, Lucia Sara; Miglietta, Riccardo; Bandello, Francesco; Rizzo, Stanislao; Mantovani, Lorenzo Giovanni (Farmeconomia. Health Economics and Therapeutic Pathways, 2015)
BACKGROUND: Vitreomacular traction (VMT) caused by vitreomacular adhesion (VMA), is a pathological condition when the vitreous humor has an abnormally strong attachment to the central part of the retina. Ocriplasmin recently approved for the treatment of VMT, including when associated with macular hole (MH) of diameter less than or equal to 400 microns, is a recombinant truncated form of the human serine protease plasmin with retained enzymatic activity, administered by intravitreal injection. We estimated long-term benefits and costs associated with the resolution of traction, following treatment with ocriplasmin versus Standard of Care (SoC), from National Health Service (NHS) perspective. METHODS: A lifetime Markov model has been adopted for Italy in order to estimate costs and outcomes, gained for patients with VMT, with and without MH, treated with ocriplasmin. Health effects have been expressed as Life Years (LY) and Quality adjusted LY gained (QALY), and estimated based on time spent in Visual Acuity (VA) states, defined by best and worst seeing eye, disutility impact associated with surgical interventions, adverse events and metamorphopsia. Deterministic and probabilistic analysis have also been conducted. RESULTS: Over a lifetime ocriplasmin versus SoC generated incremental benefits in terms of QALYs and overall treatment costs in each patients subgroups. Patients with VMT and VMT+MH treated with ocriplasmin had an incremental survival benefits of 0.1123 and 0.0772 QALYs respectively. Therefore, it is expected to come at an incremental cost of 1,873 € and 2,185 € for VMT and VMT+MH patients respectively. The associated ICER is 16,683 € and 28,294 € per QALY gained. Both sensitivity analyses for each of the subgroups confirmed the robustness of the model results. CONCLUSION: Compared to SoC, ocriplasmin is a cost effective therapy option in the treatment of VMT, including when associated with MH. [Article in Italian]